Stock liquidity and activist blockholders: friend or foe? - Chia, Yee Ee; Chia, Ricky Chee Jiun; Jude Woryanta Taunson (Taylor & Francis, 2021)
This paper investigates the effect of stock liquidity on blockholders for Malaysian public listed companies over a 19-year period from 2000 to 2018. Using five liquidity proxies, our results show a negative relationship between liquidity and blockholders. The negative effect of liquidity on blockholders is stemming from governance theory implies that greater stock liquidity decreases the cost of exit, and hence magnifies blockholders threat of exit when they are dissatisfied with company performance. Our results are robust to a battery of sensitivity tests, including endogeneity and disaggregate types of blockholders.